2017
DOI: 10.1371/journal.pntd.0005443
|View full text |Cite
|
Sign up to set email alerts
|

Protective immune responses against Schistosoma mansoni infection by immunization with functionally active gut-derived cysteine peptidases alone and in combination with glyceraldehyde 3-phosphate dehydrogenase

Abstract: BackgroundSchistosomiasis, a severe disease caused by parasites of the genus Schistosoma, is prevalent in 74 countries, affecting more than 250 million people, particularly children. We have previously shown that the Schistosoma mansoni gut-derived cysteine peptidase, cathepsin B1 (SmCB1), administered without adjuvant, elicits protection (>60%) against challenge infection of S. mansoni or S. haematobium in outbred, CD-1 mice. Here we compare the immunogenicity and protective potential of another gut-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
6
49
0
Order By: Relevance
“…Our results confirm an association of SmGAPDH with the tegumental surface of the worm. This further reconciles results that previously characterized SmGAPDH as a protective vaccine target (Argiro et al, 2000b;El Ridi and Tallima, 2013;Tallima et al, 2017;Tang et al, 2019). Before these results, how such an intracellular cytosolic enzyme might be accessed by damaging immune effectors was a conundrum.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results confirm an association of SmGAPDH with the tegumental surface of the worm. This further reconciles results that previously characterized SmGAPDH as a protective vaccine target (Argiro et al, 2000b;El Ridi and Tallima, 2013;Tallima et al, 2017;Tang et al, 2019). Before these results, how such an intracellular cytosolic enzyme might be accessed by damaging immune effectors was a conundrum.…”
Section: Discussionsupporting
confidence: 85%
“…GAPDH is best known as a key enzyme in glycolysis, facilitating the conversion of glyceraldehyde-3-phosphate (GAP) in the presence of nicotinamide adenide dinucleotide (NAD) to 1,3-bisphosphoglycerate (1,3BPG) and generating NADH (Seidler, 2013). S. mansoni GAPDH (SmGAPDH) has been previously expressed in an enzymatically active recombinant form (Argiro et al, 2000a;El Ridi et al, 2001, 2004, has been characterized as a potential vaccine candidate and has been shown to be a target for antibodies in the sera of schistosomiasisresistant individuals (Argiro et al, 2000a,b;Dessein et al, 1988;Goudot-Crozel et al, 1989;Tallima et al, 2017;Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sm CB1 is a promising vaccine candidate because its administration elicits protection against S . mansoni challenge infection in mice and hamsters [ 30 , 31 ]. A direct link with HDACs has never been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported remarkable cases of resistance to PZQ which include the development of heritable trait that maintained drug resistance to PZQ in more than six generations (Devaney, 2006;Doenhoff, Cioli & Utzinger, 2008;Fallon et al, 1996;Masamba et al, 2016;William et al, 2001). Only 13% of targeted population received praziquantel treatment, with the drug not capable of preventing reinfection, requires repeated treatment and its characterised by reduction in efficiency among population with heavy infection (Tallima et al, 2017). With the endemicity of schistosomiasis still on the increase across many countries, with increased cases of Schistosoma resistance to the most used and reliable drug PZQ.…”
Section: Discussionmentioning
confidence: 99%